Impact of high-risk optic disc on central retinal vein occlusion in patients with metabolic disorders - Si, Shancheng; Lin, Jiateng; Guo, Rong; Chen, Anming; Ji, Yicong (Frontiers in Physiology, 2024)
Purpose: To evaluate the impact of high-risk optic disc (HROD) on central retinal vein occlusion (CRVO) in patients with metabolic disorder(s). Design: Retrospective case-control study Methods: A case-control study involving CRVO patients with metabolic disorder(s) was performed. PART I. All eligible patients with CRVO were included in CRVO group, and a similar number of patients with metabolic disorder(s) without CRVO were matched by sex, age and blood glucose level in the non-CRVO group. Various parameters were compared between groups. The impact of risk factors associated with CRVO was presented as odds ratios (ORs) and 95% confidence interval (95% CI). PART II. All eyes with CRVO that underwent intravitreal treatment (IVT) with a follow-up duration of ≥ 1 year were divided into non-HROD and HROD groups, and the differences between the two groups were compared. Results: In PART I, a total of 45 and 63 eyes were enrolled in the CRVO and non-CRVO groups, respectively, with a significant statistical difference in HROD (51.16% vs. 26.98%, P=0.010) between them. In further multivariate regression analysis, HROD was the independent risk factor for CRVO (OR = 5.036, 95% CI 1.847–13.729, P=0.002). In PART II, demographic, follow-up information, treatment, and prognosis showed no significant statistical difference between the two groups (all P >0.05). Conclusions: HROD was likely to be an independent risk factor for CRVO occurrence in patients with metabolic disorder(s), but it did not affect the treatment and prognosis of CRVO eyes with HROD.